Magnesium sulphate given topically by iontophoresis for viability of random skin flaps in rats - Yu, Renato Andre [UNESP]; Brumini, Christine [UNESP]; Esteves Junior, Ivaldo [UNESP]; Ferreira, Lydia Masako; Liebano, Richard Eloin [UNESP] (Taylor & Francis As, 2009)
Our aim was to assess the effects of magnesium sulphate given by iontophoresis on the viability of random skin flaps in rats. Endovenous magnesium sulphate is used to treat pre-eclampsia and diseases of blood vessels. Iontophoresis is an electrotherapeutic method which has shown satisfactory results in controlling ischaemia within the boundaries of the area in which it was given. Forty-five adult male Wistar rats, weighing 300 to 440 g were randomly divided into three groups of 15 animals each: random skin flap (control); random skin flap treated with magnesium sulphate without electrical stimulation; and random skin flap treated with magnesium sulphate with electrical stimulation of 4 mA for 20 minutes. The treatments were applied immediately after the operation and repeated on the following two days. The percentage of necrotic area was measured on the seventh postoperative day using a paper template. For each group, the mean percentage of flap necrosis was as follows: control, 46%; magnesium sulphate without electrical stimulation, 34%; and magnesium sulphate with electrical stimulation, 42%. There was no significant difference among the groups (p=0.18). Magnesium sulphate given by iontophoresis does not increase the viability of random skin flaps in rats.
Keywords: Surgical flaps; ischemia; magnesium sulphate; iontophoresis